The Influence of Science Skills Through Scientific Learning Model In Biology Learning: A Review Study - Ezif Rizqi Imtihana; Restiana Restiana (Bioedukasi: Jurnal Pendidikan Biologi, 2023)
Scientific learning is a common approach that is quite effective in learning, especially in learning biology.  This research was conducted with the aim to find out (1) the influence of science skills through scientific learning models, (2) types of scientific learning models that affect students' science skills, and (3) natural science topics using scientific learning models that affect students' science skills.  This research was a meta-analysis study with a qualitative approach that adopted a literature review method by Durst & Edvardsson consisting of the following 4 steps. 15 articles were selected from 27 articles published in the last 5 years (2018-2022). The research article was searched using the Educational Resources Information Center (ERIC), SINTA Indonesia online database. Results of these analyses show that science skills affected through scientific learning model are 3C, thinking skill, literacy skill, and science process skill. These science skills are influenced through scientific learning model by project-based learning, problem-based learning and discovery learning. Biology topics used in this research are environment, plantae, histology, endocrine system, animal kingdom, ecosystem, and biodiversity; environment is the most commonly used topic in science learning.